“The Father of Survival Horror”: Shinji Mikami, Procedural Rhetoric, and the Collective/Cultural Memory of the Atomic Bombs - Scheiding, Ryan (Loading, 2019)
Video game “authors” use procedural rhetoric to make specific arguments within the narratives of their games. As a result, they, either purposefully or incidentally, contribute to the creation and maintenance of collective/cultural memory. This process can be identified within the directorial works of Shinji Mikami that include a set of similar general themes. Though the settings of these games differ, they include several related plot elements. These include: 1) depictions of physical and emotional trauma, 2) the large-scale destruction of cities, and 3) distrust of those in power. This paper argues that Mikami, through processes of procedural rhetoric/ authorship, can be understood as an “author” of video games that fall into the larger tradition of war and atomic bomb memory in Japan. (Also known as hibakusha (bomb-affected persons) literature). As a result, his games can be understood as a part of Japan’s larger collective/cultural memory practices surrounding the atomic bombings of Hiroshima (6 August 1945) and Nagasaki (9 August 1945). In the case of Mikami, the narratives of his games follow what Akiko Hashimoto labels as the “Long Defeat”, in which Japanese collective/cultural memory struggles to cope with the cultural trauma of the Pacific War (1931-1945). To illustrate this argument the paper engages in a close reading of Mikami’s Resident Evil, Dino Crisis, Resident Evil 4, Vanquish and The Evil Within and identifies tropes that are common to Japanese war memory and hibakusha literature.